Photonic Crystals: Optically Bistable Macroporous Photonic Crystals Enabled by Thermoresponsive Shape Memory Polymers (Advanced Optical Materials 11/2015). Issue 11 (November 2015) - Fang, Yin; Leo, Sin‐Yen; Ni, Yongliang; Yu, Long; Qi, Pengxu; Wang, Bingchen; Basile, Vito; Taylor, Curtis; Jiang, Peng
Abstract : Macroporous photonic crystals with optically bistable states are fabricated by P. Jiang and co‐workers using thermoresponsive shape memory polymers. On page 1509, the reversible transition between an ordered permanent state and a disordered temporary state during the shape memory "programming" and "recovery" processes results in tremendous changes in the appearance and optical properties of the photonic crystal membranes.